Предмет: Алгебра,
автор: Школотаааааа
Найти х
3lg(x-3) = lg(x^3-63)
Ответы
Автор ответа:
1
3lg(x - 3) = lg(x³ - 63)
lg(x - 3)³ = lg(x³ - 63)
x³ - 9x² + 27x - 27 = x³ - 63
-9x² + 27x + 36 = 0
x² - 3x - 4 = 0
x1 = -1
x2 = 4
OTVET: 4
Автор ответа:
0
task/29467905 Решить уравнение 3lg(x-3) = lg(x³-63)
----------------------
3lg(x-3) = lg(x³ - 63) ; ОДЗ: { x-3 > 0 , x³ - 63 > 0 . * * * x >∛63 * * *
lg(x-3)³ = lg(x-3) ⇔(x -3)³ = x³ - 63 ⇔x³ - 9x²+27x -27 = x³ - 63 ⇔
0 =9x² - 27x -36 ⇔ x² - 3x - 4 =0 ⇔ [ x = -1 ; x = 4 .
x = -1 ∉ ОДЗ ( посторонний корень)
ответ: 4.
Похожие вопросы
Предмет: История,
автор: MakarTrushin
Предмет: Геометрия,
автор: Аноним
Предмет: География,
автор: margoshka27
Предмет: Математика,
автор: Ymnыi